Modulation of stimulus‐specific adaptation by GABAA receptor activation or blockade in the medial geniculate body of the anaesthetized rat. (30th October 2013) - Duque, Daniel; Malmierca, Manuel S.; Caspary, Donald M.
Abstract : Key points: Neurons in the medial geniculate body (MGB), the auditory thalamus, give stronger responses to rare sounds than to repetitive sounds, a phenomenon referred to as stimulus‐specific adaptation (SSA). The present study sought to elucidate how the inhibitory thalamic circuitry acting at GABAA receptors affects the generation and/or modulation of SSA from recordings of single unit responses from MGB. Microiontophoretic application of GABAergic agonists selectively increased SSA indices, whereas application of antagonists selectively reduced SSA values. We found that GABAA ‐mediated inhibition did not generate the SSA response but regulated the magnitude of SSA sensitivity in a gain control manner. These findings advance our understanding of the role of inhibition in coding deviance detection in the MGB. Abstract: Stimulus‐specific adaptation (SSA), which describes adaptation to repeated sounds concurrent with the maintenance of responsiveness to uncommon ones, may be an important neuronal mechanism for the detection of and attendance to rare stimuli or for the detection of deviance. It is well known that GABAergic neurotransmission regulates several different response properties in central auditory system neurons and that GABA is the major inhibitory neurotransmitter acting in the medial geniculate body (MGB). The mechanisms underlying SSA are still poorly understood; therefore, the primary aim of the present study was to examine what role, if any, MGB GABAergic circuits play in the generation and/or modulation of SSA. Microiontophoretic activation of GABAA receptors (GABAA Rs) with GABA or with the selective GABAA R agonist gaboxadol significantly increased SSA (computed with the common SSA index, CSI) by decreasing responses to common stimuli while having a lesser effect on responses to novel stimuli. In contrast, GABAA R blockade using gabazine resulted in a significant decrease in SSA. In all cases, decreases in the CSI during gabazine application were accompanied by an increase in firing rate to the stimulus paradigm. The present findings, in conjunction with those of previous studies, suggest that GABAA ‐mediated inhibition does not generate the SSA response, but can regulate the level of SSA sensitivity in a gain control manner. The existence of successive hierarchical levels of processing through the auditory system suggests that the GABAergic circuits act to enhance mechanisms to reduce redundant information.